MY CART (5)

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: R

There are no items in this cart.
Continue Shopping
Menu

Relation between A.M., G.M. and H.M.

Let there are two numbers ‘a’ and ‘b’, a, b > 0

 

then AM = a+b/2

 GM =√ab

 HM =2ab/a+b

 ∴ AM × HM =a+b/2 × 2ab/a+b = ab = (√ab)2 = (GM)2

 Note that these means are in G.P.

 Hence AM.GM.HM follows the rules of G.P.

 i.e. G.M. =√A.M. × H.M.

 Now, let us see the difference between AM and GM

 AM – GM =a+b/2 – √ab

              =(√a2)+(√b)–2√a√b/2

 i.e. AM > GM

 Similarly,

 G.M. – H.M. = √ab –2ab/a+b

                  =√ab/a+b (√a – √b)2 > 0

 So. GM > HM

 Combining both results, we get

 AM > GM > HM                                                   …….. (12)

 All sequences of numbers cannot be put into A.P./G.P./H.P. Let us study these.

 Important Points:

r3 (r – 1)3 = 3 r2 – 3r + 1

r = 1 : 13 – 0 = 3 . 12 – 3 . 1 + 1

r = 2 : 23 – 13 = 3 . 22 – 3 . 2 + 1

r = 3 : 33 – 23 = 3 . 32 – 3 . 3 + 1

r = n : n3 – (n–1)3 = 3.(n2) – 3(n) + 1

Adding

n3 = 3 (12 + 22 +…+ n2) –3 (1 + 2 + 3 +…+ n) + (1 + 1 +…+ n times)

n3 = 3 Σnr=1 r2 – 3 (n(n+1))/2 + n

⇒ 3 Σnr=1 r2 = n3 + 3n(n+1)/2 – n

        = n/2 (2n2 + 3n + 1)

 Σnr=1 r2 = n(n+1)(2n+1)/6

 

To know more about the study material of engineering and medical exams, please fill up the form given below:

We promise that your information will be our little secret. To know more please see our Privacy Policy
We promise that your information will be our little secret. To know more please see our Privacy Policy

OR

Signing up with Facebook allows you to connect with friends and classmates already using askIItians. It’s an easier way as well. “Relax, we won’t flood your facebook news feed!”